Microextraction Techniques with Deep Eutectic Solvents - Plastiras, Orfeas-Evangelos (Molecules, 2020)
In this review, the ever-increasing use of deep eutectic solvents (DES) in microextraction techniques will be discussed, focusing on the reasons needed to replace conventional extraction techniques with greener approaches that follow the principles of green analytical chemistry. The properties of DES will be discussed, pinpointing their exceptional performance and analytical parameters, justifying their current extensive scientific interest. Finally, a variety of applications for commonly used microextraction techniques will be reported.